Aggressive cutaneous squamous cell carcinoma in a hydroxyurea‐ and ruxolitinib‐pretreated patient with polycythaemia vera. (2nd December 2021) - Gambichler, T.; Stockfleth, E.; Susok, L.
Abstract: Hydroxyurea and ruxolitinib are frequently used to treat myeloproliferative disorders, including polycythaemia vera, and chronic treatment is associated with many cutaneous adverse effects such as the development of aggressive non‐melanoma skin cancer (NMSC). We report an 85‐year‐old man with a history of hydroxyurea‐ and ruxolitinib‐treated polycythaemia vera who was referred for the management of progressively growing tumours on his scalp. Histopathology of the largest scalp lesion revealed a partly desmoplastic cutaneous squamous carcinoma with perineural invasion. Initial imaging revealed metastatic disease in cervical lymph nodes, bones and lungs. The scalp lesions were successfully treated with bleomycin‐based electrochemotherapy. Under initial systemic therapy using four cycles of cetuximab, metastatic disease progressed. Following the approval by the health insurance, compassionate use of pembrolizumab monotherapy was initiated. After three cycles of pembrolizumab, however, metastatic disease further progressed and the patient finally died from global respiratory insufficiency. The present case exemplifies the cutaneous adverse effects of long‐term hydroxyurea and ruxolitinib therapy, frequently resulting in highly aggressive NMSCs that are usually not responsive to systemic treatments even such as immune checkpoint inhibitors.